Mutating chikungunya virus non‐structural protein produces potent live‐attenuated vaccine candidate - Yi‐Hao Chan; Teck‐Hui Teo; Age Utt; Jeslin JL Tan; Siti Naqiah Amrun; Farhana Abu Bakar; Wearn‐Xin Yee; Etienne Becht; Cheryl Yi‐Pin Lee; Bernett Lee; Ravisankar Rajarethinam; Evan Newell; et al. (EMBO Molecular Medicine)
Abstract Currently, there are no commercially available live‐attenuated vaccines against chikungunya virus (CHIKV). Here, CHIKVs with mutations in non‐structural proteins (nsPs) were investigated for their suitability as attenuated CHIKV vaccines. R532H mutation in nsP1 caused reduced infectivity in mouse tail fibroblasts but an enhanced type‐I IFN response compared to WT‐CHIKV. Adult mice infected with this nsP‐mutant exhibited a mild joint phenotype with low‐level viremia that rapidly cleared. Mechanistically, ingenuity pathway analyses revealed a tilt in the anti‐inflammatory IL‐10 versus pro‐inflammatory IL‐1β and IL‐18 balance during CHIKV nsP‐mutant infection that modified acute antiviral and cell signaling canonical pathways. Challenging CHIKV nsP‐mutant‐infected mice with WT‐CHIKV or the closely related O'nyong‐nyong virus resulted in no detectable viremia, observable joint inflammation, or damage. Challenged mice showed high antibody titers with efficient neutralizing capacity, indicative of immunological memory. Manipulating molecular processes that govern CHIKV replication could lead to plausible vaccine candidates against alphavirus infection.